Optimasi Gangguan Surja Petir Dengan Pengaturan Jarak Lightning Arrester - Nurmiati Pasra; Samsurizal Samsurizal; Kartika Tresya (Setrum : Sistem Kendali-Tenaga-elektronika-telekomunikasi-komputer, 2022)
Several cities in the Indonesian region are tropical areas that have a fairly high level of lightning insecurity, one of which is the Jayapura city. Demographic conditions make up to the occurrence of lightning strikes and fall into the category of regions that have a fairly high level of lightning insecurity. One of the causes of frequent interference in high-voltage systems comes from lightning. For this reason, it is necessary to optimize the interference that may occur by setting the distance between the lightning arrester and the transformer so as to minimize the level of interference that can occur due to lightning. Lightning arrester is one of the protection tools used to protect equipment against short circuit and lightning. From the results and analysis that has been done obtained results with a distance of 4.11 m and 4.40m which has an impulse voltage value due to surja that arrives at its transformer at skyline substation of 114.22 kV and 114.80 kV.  While the optimal distance from the placement of the lightning arrester with the transformer is at a distance of 0.58m at that distance obtained a large value of impulse voltage due to surja that arrives at the transformer of 107.16 kV. The value of impulse voltage due to surja is smaller when compared to the value of impulse voltage due to surja obtained from the lightning arrester separated from the transformer. So that in this study it can be concluded that a good lightning arrester placement is required to be as close as possible to the equipment it protects in order to neutralize the disturbances that can occur.